2003
DOI: 10.1097/00006534-200301000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bone Morphogenetic Proteins during Mandibular Distraction Osteogenesis

Abstract: Distraction osteogenesis is a form of in vivo tissue engineering in which the gradual separation of cut bone edges results in the generation of new bone. In this study, the temporal and spatial expression of bone morphogenetic proteins (BMPs) 2, 4, and 7 was examined in a rabbit model of mandibular distraction osteogenesis. Fourteen skeletally mature male rabbits were studied. After osteotomy, a distractor was applied to one side of the mandible. After 1 week of latency, distraction was initiated at 0.25 mm ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 13 publications
5
36
0
6
Order By: Relevance
“…Pre-myogenic cells are capable of differentiating into chondrogenic or osteogenic cells when exposed to BMPs [7], and signaling of BMP2 initiating from the vasculature may attract circulating cells of osteoblastic lineage [46]. During distraction osteogenesis, the spatial patterns of VEGF and BMP2 expression are tightly linked [12], and there is a temporal correspondence between BMP2 expression and the amount of vascularized connective tissue in the distraction gap during the first two weeks of distraction [47]. Moreover, inhibition of angiogenesis during distraction osteogenesis [11] and fracture repair [23] prevents bone formation and leads to fibrous non-union.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-myogenic cells are capable of differentiating into chondrogenic or osteogenic cells when exposed to BMPs [7], and signaling of BMP2 initiating from the vasculature may attract circulating cells of osteoblastic lineage [46]. During distraction osteogenesis, the spatial patterns of VEGF and BMP2 expression are tightly linked [12], and there is a temporal correspondence between BMP2 expression and the amount of vascularized connective tissue in the distraction gap during the first two weeks of distraction [47]. Moreover, inhibition of angiogenesis during distraction osteogenesis [11] and fracture repair [23] prevents bone formation and leads to fibrous non-union.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining of cellular and extracellular proteins has been used in mandibular [20], long bone distraction osteogenesis [21-24], and bone healing [13-15] studies. We employed this technique to semi-quantitatively evaluate our results based on the percentage of positively stained cells using the following grading scheme: +, 25% of the cells stained positively for the protein of interest; ++, 25 to 50% of the cells stained positively; +++, 50 to 75% of the cells stained positively; ++++, more than 75% of the cells stained positively; -, no cells stained positively.…”
Section: Methodsmentioning
confidence: 99%
“…18,50 It has been reported that BMP-7 plays a role similar to that of BMP-2 and BMP-4 in distraction osteogenesis 48 ; however, most experiments have detected only weak levels or no expression of BMP-7 during distraction osteogenesis. 19,49,51 …”
Section: The Role Of Bmp In Distraction Osteogenesismentioning
confidence: 99%